The Growing Skyline of Advanced Hepatocellular Carcinoma Treatment: A Review - Francesca Matilde Schipilliti; Ingrid Garajová; Giulia Rovesti; Rita Balsano; Federico Piacentini; Massimo Dominici; Fabio Gelsomino (MDPI AG, 2021)
Hepatocellular carcinoma (HCC) is the main type of liver cancer. In the majority of cases, HCC is diagnosed at the advanced stage, leading to poor prognosis. In recent years, many efforts have been devoted to investigating potential new and more effective drugs and, indeed, the treatment armamentarium for advanced HCC has broadened tremendously, with targeted- and immune-therapies, and probably the combination of both, playing pivotal roles. Together with new established knowledge, many issues are emerging, with the role of neoadjuvant/adjuvant settings, the definition of the best transitioning time from loco-regional treatments to systemic therapy, the identification of potential predictive biomarkers, and radiomics being just some of the topics that will have to be further explored in the next future. Clearly, the current COVID-19 pandemic has influenced the management of HCC patients and some considerations about this topic will be elucidated.